Real-world effectiveness of casirivimab and imdevimab among patients diagnosed with COVID-19 in the ambulatory setting: a retrospective cohort study using a large claims database. Issue 12 (19th December 2022) - Hussein, Mohamed; Wei, Wenhui; Mastey, Vera; Sanchez, Robert J; Wang, Degang; Murdock, Dana J; Hirshberg, Boaz; Weinreich, David M; Jalbert, Jessica J
Abstract : Objective: To assess the real-world effectiveness of casirivimab and imdevimab (CAS+IMD) versus no COVID-19 antibody treatment among patients diagnosed with COVID-19 in the ambulatory setting, including patients diagnosed during the Delta-dominant period prior to Omicron emergence. Design: Retrospective cohort study. Setting: Komodo Health closed claims database. Participants: 13 273 128 patients diagnosed with COVID-19 (December 2020 through September 2021) were treated with CAS+IMD or untreated but treatment eligible under the Emergency Use Authorization (EUA). Each treated patient was exact and propensity score matched without replacement to up to five untreated EUA-eligible patients. Interventions: CAS+IMD. Primary and secondary outcome measures: Composite endpoint of 30-day all-cause mortality or COVID-19-related hospitalisation. Kaplan-Meier estimators were used to calculate outcome risks overall and across subgroups: age, COVID-19 vaccination status, immunocompromised status, and timing of diagnosis (December 2020 to June 2021, and July to September 2021). Cox proportional hazards models were used to estimate adjusted HRs (aHRs) and 95% CIs. Results: Among 75 159 CAS+IMD-treated and 1 670 338 EUA-eligible untreated patients, 73 759 treated patients were matched to 310 688 untreated patients; matched patients were ~50 years, ~60% were women and generally well balanced across risk factors. The 30-day risk of the composite outcome was 2.1% and 5.2% in the CAS+IMD-treated and CAS+IMD-untreated patients, respectively; equivalent to a 60% lower risk (aHR 0.40; 95% CI, 0.38 to 0.42). The effect of CAS+IMD was consistent across subgroups, including those who received a COVID-19 vaccine (aHR 0.48, 95% CI, 0.41 to 0.56), and those diagnosed during the Delta-dominant period (aHR 0.40, 95% CI, 0.38 to 0.42). Conclusions: The real-world effectiveness of CAS+IMD is consistent with the efficacy for reducing all-cause mortality or COVID-19-related hospitalisation reported in clinical trials. Effectiveness is maintained across patient subgroups, including those prone to breakthrough infections, and was effective against susceptible variants including Delta.